2022
DOI: 10.3389/fpsyg.2022.982704
|View full text |Cite
|
Sign up to set email alerts
|

Learning to play a musical instrument in the middle school is associated with superior audiovisual working memory and fluid intelligence: A cross-sectional behavioral study

Abstract: Music training, in all its forms, is known to have an impact on behavior both in childhood and even in aging. In the delicate life period of transition from childhood to adulthood, music training might have a special role for behavioral and cognitive maturation. Among the several kinds of music training programs implemented in the educational communities, we focused on instrumental training incorporated in the public middle school curriculum in Italy that includes both individual, group and collective (orchest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 200 publications
0
3
0
Order By: Relevance
“…The most positive findings were observed for inhibitory control (Bolduc et al, 2021;Degé and Frischen, 2022;Rodriguez-Gomez and Talero-Gutiérrez, 2022;Schellenberg and Lima, 2024). The association between music training and working memory (both verbal and visual) has been shown predominantly in studies with school-aged rather than preschool-aged children (Bergman Nutley et al, 2014;Kausel et al, 2020;Nie et al, 2022;Vuust et al, 2022). We found only two studies where music training has been shown to influence the development of cognitive flexibility in preschoolers (Shen et al, 2019;Ilari et al, 2021).…”
Section: Music Training and Ef Development In Preschool Childrenmentioning
confidence: 67%
“…The most positive findings were observed for inhibitory control (Bolduc et al, 2021;Degé and Frischen, 2022;Rodriguez-Gomez and Talero-Gutiérrez, 2022;Schellenberg and Lima, 2024). The association between music training and working memory (both verbal and visual) has been shown predominantly in studies with school-aged rather than preschool-aged children (Bergman Nutley et al, 2014;Kausel et al, 2020;Nie et al, 2022;Vuust et al, 2022). We found only two studies where music training has been shown to influence the development of cognitive flexibility in preschoolers (Shen et al, 2019;Ilari et al, 2021).…”
Section: Music Training and Ef Development In Preschool Childrenmentioning
confidence: 67%
“…Another recent article by Lippolis et al, (2022) includes an updated bibliography on the subject of possible transfer to near‐ and far‐abilities and examines the influence of training in instrumental music on working memory and fluid intelligence, thanks to a methodology apt at being carried out in the environment of public education (for a previous investigation in the same context, see Carioti et al, 2019). A cohort of 285 children aged 10 to 14 years was tested with a battery of tests including Jack&Jill, matrix reasoning, and listening tasks.…”
Section: Psychopathological Psychological and Cognitive Differencesmentioning
confidence: 99%
“…Though there is debate about whether and how musical training transfers to skills in other domains (see Sala &Gobet, 2020 andBigand &Tillman, 2022), converging evidence from several longitudinal studies, such as the LongGold project (https://longgold.org/; Müllensiefen et al, 2022;Müllensiefen et al, 2015), suggests that musical training may benefit cognitive abilities throughout middle childhood and into adolescence (for a meta-analysis, see Román-Caballero et al, 2022). Specifically, musical training during this window leads to improvements in inhibitory control (Hennesy et al, 2019) and working memory (Lippolis et al, 2022), as well as greater activation of brain areas supporting inhibition (Sachs et al, 2017) and brain structure volumes of auditory and motor areas (Hyde et al, 2009). Moreover, s Indeed, studies have shown the immediate importance of musical engagement in the home in developmental samples, finding positive impacts on language (Papadimitriou et al, 2021) and auditory perception (for a review, see Putkinen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%